Automatic Watering System Berbasis Internet of Thing (IoT) untuk Peningkatan Produksi Pertanian - Marwondo; Nursyanti , Reni; Kurnia , Mohamad Erlangga (Pusat Studi Teknologi Informasi Fakultas Ilmu Komputer Universitas Bandar Lampung, 2025)
Indonesia, as an agrarian country, faces challenges in efficient agricultural irrigation, primarily due to conventional watering methods that lack precision. The application of Internet of Things (IoT) technology offers a promising solution to improve water efficiency and agricultural productivity. This community service program aimed to enhance the understanding and skills of students and teachers at SMKN PP Lembang in designing and implementing an IoT-based automatic watering system. The program was conducted in three phases: preparation, training, and evaluation, using an educational and participatory approach. The results showed a significant increase in participants’ understanding of IoT concepts and applications—from 45% before training to 100% afterward. Participants also demonstrated strong readiness to adopt this technology in daily agricultural practices. This program proved effective in supporting the transformation of agriculture towards a more modern, precise, and sustainable system.